Evaluation of seminal fructose and citric acid levels in men with fertility problem - Makhadumsab M Toragall; Sanat K Satapathy; Girish G Kadadevaru; Murigendra B Hiremath (Wolters Kluwer Medknow Publications, 2019)
Context: Male infertility is a medical problem, attributed to 50% of infertility. Seminal plasma can be an anticipating factor as it comprises secretions of accessory sex gland, thus offering novel and precise ways to understand potential roles of these biochemical markers in male infertility. Aim: The objective of this study was to assess the correlation between biochemical markers and sperm parameters in envisaging male infertility. Subjects and Design: We enlisted 105 men with fertility issue as patients and 25 fertile men as controls to evaluate the sperm parameters and biochemical markers, namely fructose and citric acid in ascertaining male infertility. Materials and Methods: The semen samples from patients were collected properly and analyzed according to the World Health Organization-2010 manual. Later samples were centrifuged, seminal plasma was collected, and biochemical markers assessment was carried out by standard protocols. Statistics: Descriptive statistics, independent t-test, one-way ANOVA, and Pearson correlation were used for statistical analysis of different variables using SPSS 20.0. The mean sperm count and motility by all infertile conditions displayed a significant difference when compared with the controls (P < 0.05). Results: The mean fructose levels of oligozoospermia showed a nonsignificance difference when compared with controls (P < 0.05). Asthenozoospermia, asthenoteratozoospermia, and azoospermia had a significance difference (P < 0.05) for citric acid levels. Pearson correlation coefficient showed significant negative correlation of sperm count (r = −0.564) and sperm motility (r = −0.574) with fructose levels. Whereas seminal citric acid concentration had a positive correlation with sperm count (r = 0.458) and sperm motility (r = 0.446). Conclusion: Therefore, evaluation of certain biochemical markers of seminal fluid may benefit in understanding the functionality of accessory glands which subsidizes significantly to the seminal volume.